Late Adolescence Behavior About Preconception Care During The Pandemic - Yurenda Aurelia; Gita Kostania; Sumy Dwi Antono; Herawati Mansur (Poltekkes Kemenkes Surakarta, 2021)
Background: The number of early marriages in Malang City increases every year, but health problems such as obesity, CED, smoking and drinking alcohol behavior, premarital sex, are still common. Thus, at this phase it is important to start planning and preparing for the future, one of which is through preconception care. The purpose of this study is to describe the late adolescents behaviour regarding preconception care in Sumbersari, Malang. Methods: The design of this research is descriptive quantitative with a survey approach. The sample in this study were late adolescent aged 18-22 years old in Sumbersari, Malang and obtained 70 samples by using purposive sampling. Data of this study was collected online by using google forms. The tool of collecting data was researcher-made questionnaire which consist of 4 indicators (life style, nutritional preparation, health reproduction, and substances exposure). From the validity and reliability test of the questionnaire obtained 26 questions for boys and 25 questions for girls. Analysis data procedure was using descriptive analysis techniques. Results: From 70 late adolescent obtained that their preconception care behavior was mostly in the enough category with 53.3% in men and 60% in women. Conclusion: Based on the results of the study, it is known that the preconception care behaviour in adolescents during the pandemic is sufficient. It means that preconception care behaviour in adolescents still requires improvement.